Estimation of median LC50 and toxicity of environmentally relevant concentrations of thiram in Labeo rohita - Sana Alam; Gulnaz Afzal; Riaz Hussain; Hafiz Muhammad Ali; Amtul Sami; Rabbiah Manzoor Malik; Raheela Jabeen; Farid Shokry Ataya; Kun Li (npj Clean Water, 2025)
Abstract Thiram is a widely used fungicide in agricultural practices as spraying on crops and grains storage but its potential adverse effects on non-target aquatic organisms have raised serious concerns. In this study, firstly LC50 value of thiram has been determined as 0.744 mg/L for the first time in Labeo rohita and then, the fish were exposed to different sub-lethal concentrations of thiram (40 μg/L, 80 μg/L and 120 μg/L) to evaluate the effects on tissue growth, oxidative stress, anti-oxidant enzymes and histo-pathological parameters at days-20, 40 and 60 of the experiment. There observed a significant (p < 0.05) decrease in the body weight while a significant increase in the relative (p < 0.05) and absolute (p < 0.05) weights of kidneys, heart and brain was found. Hematological analysis showed a significant (p < 0.05) increase in leukocytes and neutrophils while lymphocytes and monocytes, RBCs and hemoglobin concentration were significantly (p < 0.05) decreased. Serum biochemical parameters revealed a significant (p < 0.05) increase in urea and hepatic enzymes while a significant (p < 0.05) decrease in total proteins, albumin and creatinine were observed at higher doses (80 μg/L and 120 μg/L) of thiram. Oxidative stress parameters; ROS and TBARS were increased significantly (p < 0.05) while antioxidant enzymes (CAT, SOD, POD, GSH) showed a significant (p < 0.05) decrease in the treated groups compared to the control. Moreover, comet assay revealed significant (p < 0.05) DNA damage in the isolated cells of kidneys, heart and brain at higher doses (80 μg/L and 120 μg/L) of thiram that was further confirmed by histo-pathological alterations in these tissues. The findings demonstrate that thiram severely pollute the marine eco-system and is quite hazardous for aquatic species by causing severe health effects even at sub-lethal concentrations and thus, render the apparently clean water to be unfit for animal and human consumption.